Dialektika ontologis “miskin dalam roh” dan “kaya di hadapan Allah”: Reevaluasi filologis Matius 5:3 dan Lukas 12:21 terhadap terjemahan LAI - Rimun, Robinson (KURIOS, 2025)
Matthew 5:3 serves as the theological prolegomenon to the Ser-mon on the Mount and undergoes semantic shifts in Indonesian translation. This article critically evaluates the Indonesian Bible Society's (LAI) translation of "poor before God" by comparing it with the Greek text ptōchoi tō pneumati (NA28). Employing grammatical-historical hermeneutics and redaction criticism, this study identifies a gap in Indonesian biblical discourse that neglects the syntactic function of the dative of respect in the grammatical structure of Matthew 5. The analysis encompasses participial clauses and the dialogical-imperative framework that constructs the mes-sage of "better righteousness" and compares it with Luke 12:21 regarding the orientation of being "rich toward God" (ploutōn eis theon). Findings indi-cate that while LAI's translation has pragmatic-relational value, the terminology "poor in spirit" more accurately preserves the introspective inward dimension and ontological status of the ideal disciple in Matthew's Narrative. This research challenges prosperity theology and proposes a transformation of ecclesiological praxis oriented toward social justice as the fruit of genuine spiritual poverty.   Abstrak Matius 5:3 merupakan prolegomena khotbah di Bukit yang mengalami pergeseran semantik dalam penerjemahan Indonesia. Artikel ini mengevaluasi kritis pilihan terjemahan Lembaga Alkitab Indonesia (LAI) "miskin di hadapan Allah" melalui komparasi dengan teks Yunani ptōchoi tō pneumati (NA28). Menggunakan hermeneutika gramatikal-historis dan kritik redaksi, penelitian ini mengidentifikasi kesenjangan dalam diskursus biblika Indonesia yang mengabaikan fungsi sintaksis dativus of respect dalam struktur gramatikal Matius 5. Analisis mencakup klausa partisipial dan bingkai dialogis-imperatif yang membangun pesan "kebenaran yang lebih baik", serta komparasi dengan Lukas 12:21 mengenai orientasi "kaya terhadap Allah" (ploutōn eis theon). Temuan menunjukkan bahwa meskipun terjemahan LAI memiliki nilai pragmatis-relasional, terminologi "miskin dalam roh" lebih akurat dalam mempertahankan dimensi introspektif batiniah dan status ontologis murid ideal dalam narasi Matius. Penelitian ini menantang teologi kemakmuran dan mengusulkan transformasi praksis eklesiologis berorientasi keadilan sosial sebagai buah kemiskinan spiritual sejati.